A linear relationship between lamotrigine and GABA in cerebrospinal fluid [Beyin omurilik sıvısında lamotrijin ve GABA arasında lineer ilişki] - KARAALP, ATİLA (Marmara University, 2011)
The γ-amino butyric acid (GABA)-mediated neurotransmission is useful in treating conditions like anxiety, sleep disturbances, depression and bipolar disorders. The aim of the present study is to supply evidence about neurochemical effects of acute lamotrigine treatment on GABA and L-glutamic acid levels in the cerebrospinal fluid of Wistar Albino rats and the involvement of cholinergic system. The day after the placement of concentric microdialysis probes into the lateral ventricles of rats, microdialysis experiments were performed in conscious rat model. The rats either received intraperitoneal injections of physiological saline or 20 mg/kg lamotrigine. For assessing the cholinergic involvement 0.5 mg/kg physostigmine or 2 mg/kg atropine sulfate pre-treatments were given prior to lamotrigine injection. GABA, L-glutamic acid and lamotrigine concentrations in the dialysates were analyzed using High Performance Liquid Chromatography. Saline produced no change in GABA or L-glutamic acid levels, but lamotrigine treatment significantly elevated GABA concentrations (p<0.05). Pre-treatment with physostigmine or atropine sulfate did not affect either GABA or L-glutamic acid levels siginificantly. Physostigmine or atropine sulfate pre-treatments did not affect the lamotrigine-induced GABA levels. The results may imply that lamotrigine-induced GABA plays a role in the pharmacological effects of lamotrigine where a linear relationship exists between lamotrigine and GABA. However, central cholinergic system fails to affect lamotrigine-induced GABA release.
Keywords: Cholinergic system; Conscious rat model; Glutamate; Microdialysis